Glasgow prognostic score is a prognosis predictor for patients with endometrial cancer. (March 2017) - Saijo, Masayuki; Nakamura, Keiichiro; Masuyama, Hisashi; Ida, Naoyuki; Haruma, Tomoko; Kusumoto, Tomoyuki; Seki, Noriko; Hiramatsu, Yuji
Abstract: Objective: This study investigated whether the inflammation-based Glasgow prognostic score (GPS) predicted the prognosis of patients with endometrial cancer (EC) in terms of progression-free survival (PFS) and overall survival (OS). Study design: Pretreatment GPS was examined to determine the correlations with recurrence and survival in 431 patients with EC. Statistical analyses were performed using the Mann–Whitney U test. PFS and OS were analyzed using the Kaplan–Meier method. Cox's proportional hazard regression was used for univariate and multivariate analyses. Results: Median PFS and OS were 49.7 and 52.7 months, respectively. The follow-up range was 1 to 140 months. Kaplan–Meier analysis revealed that patients with EC cancer and high GPS (GPS 2) had a shorter PFS and OS than those with lower GPS (GPS 0 + 1) (PFS: P < 0.001; OS; P < 0.001). On multivariate analysis, GPS (GPS 2) was an independent predictor of both recurrence (P < 0.001) and survival (P < 0.001) for all cases of EC. Conclusion: GPS can be useful as an indicator of poor prognosis in patients with EC.